Các hợp chất isoflavon và dihydrophenanthren từ cây sưa Bắc Bộ (Dalbergia tonkinensis) - Tuấn, Trần Anh; Đạt, Nguyễn Tiến; Nam, Nguyễn Hoài; Hưng, Nguyễn Quang; Hợi, Trần Minh; Thái, Trần Huy; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2014)
The plants of the Dalbergia genus have been used for a long time in Vietnamese traditional medicine. In our continuing study on the chemical constituent and biological activities of medicinal plants, a phytochemical investigation of the methanol extract of Dalbergia tonkinensis led to the isolation of two isoflavones (1, 2) and a dihydrophenanthrene (3). Their structures were identified by spectroscopic methods including ESI-MS, 1D- and 2D-NMR in comparison with the literature. Compound 3 was found for the first time from the Dalbergia species.